2001
DOI: 10.1001/archinte.161.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Routine Measurement of Pleural Fluid Amylase Is Not Indicated

Abstract: The routine measurement of pleural fluid amylase levels is neither clinically indicated nor cost-effective. We suggest that pleural fluid serum amylase levels be measured only if there is a pretest suspicion of acute pancreatitis, chronic pancreatic disease, or esophageal rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 18 publications
0
29
0
7
Order By: Relevance
“…It is reported that nearly half of the patients with ARPE have also increased level of serum amylase produced by ectopic tumor cells (Salt and Schenker, 1976;Devuyst et al, 1990;Branca et al, 2001;Light, 2007;Hooper et al, 2010). On the other hand PA may accumulate in pleural space due to tumoral obstruction of lymphatics (Branca et al, 2001). Pleural amylase levels were investigated by many studies and some of them reported a significant correlation between PA and lung cancers particularly adenocarcinoma (Foresti et al, 1994;Gupta et al, 2001;Villena et al, 2002;) Villena et al (2002) reported a positive correlation between increased levels of amylase in ARPE and malignancy and the average expectancy of life also decreased by high PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that nearly half of the patients with ARPE have also increased level of serum amylase produced by ectopic tumor cells (Salt and Schenker, 1976;Devuyst et al, 1990;Branca et al, 2001;Light, 2007;Hooper et al, 2010). On the other hand PA may accumulate in pleural space due to tumoral obstruction of lymphatics (Branca et al, 2001). Pleural amylase levels were investigated by many studies and some of them reported a significant correlation between PA and lung cancers particularly adenocarcinoma (Foresti et al, 1994;Gupta et al, 2001;Villena et al, 2002;) Villena et al (2002) reported a positive correlation between increased levels of amylase in ARPE and malignancy and the average expectancy of life also decreased by high PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…A veces se observan partículas de comida. De todas formas, su determinació n rutinaria no está justificada 43 .…”
Section: Amilasaunclassified
“…In der Literatur wurde die Fistelung ins Mediastinum, nach thorakal, zum Kolon und in die Leber beschrieben [2]. Pankreatikopleurale Fisteln werden insbesondere bei der chronischen Pankreatitis ethyltoxischer Genese beobachtet und entstehen als Folge rupturierter Pseudozysten oder fortschreitender Organnekrosen, insbesondere nach rezidivierenden akuten Schüben [3,4]. Davon differenzialdiagnostisch abgegrenzt werden müssen rezidivierende Pleuraergüsse durch transdiaphragmale Lymphfisteln oder häufig auftretende Pleuraergüsse im Rahmen einer akuten Pankreatitis.…”
Section: Pankreasfisteln Epidemiologieunclassified
“…Eine weitere therapeutische interventionellendoskopische Option stellt die Platzierung einer nasopankreatischen Sonde direkt in den Fistelgang dar [3,4]. …”
Section: Therapieunclassified